If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8q + -35 = 61 Reorder the terms: -35 + 8q = 61 Solving -35 + 8q = 61 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 8q = 61 + 35 Combine like terms: -35 + 35 = 0 0 + 8q = 61 + 35 8q = 61 + 35 Combine like terms: 61 + 35 = 96 8q = 96 Divide each side by '8'. q = 12 Simplifying q = 12
| 21=48-9q | | 53=6p+11 | | 30-5p=5 | | 60-4x=8 | | 14=47-3x | | 75-8x=3 | | 25x^3=0 | | (3x-18)/(6x-15) | | 4x^3-28x^2+48x=4 | | -5(2t+1)=-65 | | -10(s+1)=-83 | | 16=56-8x | | 6(4s+4)=192 | | x+(x(2)+2.5)=471.8 | | 5(2l+6)=80 | | 6=30-6x | | 3a+7a-4a= | | 2(a-8)=80 | | 26=4a-22 | | 12a-25=35 | | 4(3x-1)-2x=56 | | 50=7a-6 | | 7x+1250=1264 | | 21+9a=66 | | 3e^-(t/0.48) | | 236x-1888=0 | | x+(x+30500)=190500 | | 5-(3x)=0 | | 5-(3-x)=5 | | 2(x+5)+8= | | 4(3+h)-2(5+3h)= | | -3(y/1)= |